The book of two ways [compact disc, unabridged] : a novel - Picoult, Jodi, 1966- (Random House Audio, 2020)
Everything changes in a single moment for Dawn Edelstein. She's on a plane when the flight attendant makes an announcement: prepare for a crash landing. She braces herself as thoughts flash through her mind. The shocking thing is, the thoughts are not of her husband, but a man she last saw fifteen years ago: Wyatt Armstrong. Dawn, miraculously, survives the crash, but so do all the doubts that have suddenly been raised.